2018
DOI: 10.1111/echo.14026
|View full text |Cite
|
Sign up to set email alerts
|

Frequent premature atrial contractions impair left atrial contractile function and promote adverse left atrial remodeling

Abstract: Patients with frequent PACs have reduced LA peak contractile strain and strain rates and larger LAVI compared to controls. Frequent PACs are an independent predictor of reduced LA peak contractile strain and strain rate. These findings support the hypothesis that frequent PACs impair LA contractile function and promote adverse LA remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…One possible explanation is that frequent PAC may adversely affect hemodynamics resulting in unfavorable reverse remodeling. Indeed, current study demonstrated that increased PAC burden was associated with impaired LA function and LA enlargement in individuals even without AF . On the other hand, frequent PAC might represent more advanced LA structural remodeling.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…One possible explanation is that frequent PAC may adversely affect hemodynamics resulting in unfavorable reverse remodeling. Indeed, current study demonstrated that increased PAC burden was associated with impaired LA function and LA enlargement in individuals even without AF . On the other hand, frequent PAC might represent more advanced LA structural remodeling.…”
Section: Discussionmentioning
confidence: 51%
“…Indeed, current study demonstrated that increased PAC burden was associated with impaired LA function and LA enlargement in individuals even without AF. 32 On the other hand, frequent PAC might represent more advanced LA structural remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in patients with 500 PACs per day on initial monitoring and either a recent stroke or a ESVEA and structural disease of the atria Excessive AE could also be an electrocardiographic marker of an underlying fibrotic atrial cardiomyopathy where AF is a mere manifestation and not necessarily the primary driver of a diseased atrium, as suggested by Kottkamp. 18 In support of this interpretation, a study by John et al 19 demonstrated that subjects with frequent PAC (.100 per 24 hours) and no AF were associated with both structural and functional changes in the left atrium (LA) with an increased LA volume index and reduced LA strain compared with controls. In our subgroup analysis there was no statistical interaction between LAE and ESVEA on a multiplicative scale, and adding LAE to the model did not attenuate the results, suggesting that ESVEA increases the risk of incident AF independently of LAE.…”
Section: Sensitivity Analysismentioning
confidence: 96%
“…These observations may be associated with increased β-blocker use in the AD-AF group. Patients with AD-AF had higher PAC burden (median [IQR] 0.82% [0.21-2.24%] vs. 0.14% [0.03-0.56%]), more PAC runs (median [IQR] 7 vs. 2 [0-5]), and longer PAC runs (median [IQR] 8 [4][5][6][7][8][9][10][11][12][13][14][15][16] vs. 4 [2][3][4][5][6][7][8][9] beats) than those with ND-AF (all P<0.001). Regarding echocardiographic parameters, patients with AD-AF had a larger LA diameter (36±6 vs. 34±6 mm; P=0.014) and higher LAVI (36±16 vs. 30±11 mL/m 2 ; P=0.015) than those with ND-AF.…”
Section: Parameters In the 24-h Ecg Discriminating And Predicting Afmentioning
confidence: 99%
“…observed that rapid runs of premature atrial contraction (PAC) precede the development of AF, and repeated episodes of AF can cause electrical or structural remodeling (or both) of the atrial muscle. 3,4 Previous studies have shown that a high PAC burden is an indicator for the development of AF; however, there is no universal agreement regarding the cut-off value for PAC burden, with few validation data. 5-10 Therefore, we sought to derive a specific PAC burden discriminating patients with and without AF using a single 24-h ECG, and to verify its predictive value, while exploring the diagnostic utility of TTE parameters representing enlargement of the left atrium (LA) or ventricular diastolic dysfunction, both of which are known predictors of AF.…”
mentioning
confidence: 99%